2018
DOI: 10.1093/mnras/sty3061
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-periodic oscillations, trapped inertial waves, and strong toroidal magnetic fields in relativistic accretionwhen th discs

Abstract: The excitation of trapped inertial waves (r-modes) by warps and eccentricities in the inner regions of a black hole accretion disc may explain the high-frequency quasiperiodic oscillations (HFQPOs) observed in the emission of Galactic X-ray binaries. However, it has been suggested that strong vertical magnetic fields push the oscillations' trapping region toward the innermost stable circular orbit (ISCO), where conditions could be unfavourable for their excitation. This paper explores the effects of large-scal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
(65 reference statements)
1
10
0
Order By: Relevance
“…forces influence the orbit of the spots. In some cases this may be established by a high degree of magnetic coupling or viscosity within the putative disk which these spots may be part of (Mondal &Mukhopadhyay 2018, andDewberry, Latter &Ogilvie 2019). This is also demonstrated in Fig.4 in which we show the possible spin a as a function of the orbiting spot radial distances.…”
Section: Pos(apcs2018)048supporting
confidence: 61%
“…forces influence the orbit of the spots. In some cases this may be established by a high degree of magnetic coupling or viscosity within the putative disk which these spots may be part of (Mondal &Mukhopadhyay 2018, andDewberry, Latter &Ogilvie 2019). This is also demonstrated in Fig.4 in which we show the possible spin a as a function of the orbiting spot radial distances.…”
Section: Pos(apcs2018)048supporting
confidence: 61%
“…The appearance of multiple HFQPOs with frequencies in nearinteger ratios in some BHBs (in particular GRO J1655-40) has led to the development of models that appeal to resonances between either fluid 'blobs' orbiting at radii where κ and Ω z achieve the same commensurability , or the global acoustic oscillations of narrow, pressure-supported, non-Keplerian accretion tori (Rezzolla et al 2003;Blaes et al 2006;Horák 2008;Fragile et al 2016). Amongst several problems, it is unclear how such oscillations achieve observable amplitudes (see discussion in Dewberry et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Eccentric waves in the inner region of XRBs are of interest as a driving mechanism for high frequency quasi-periodic oscillations (QPOs), a type of variability observed in the Xray spectra of some black hole systems, via the excitation of trapped inertial waves (Kato 2008;Ferreira & Ogilvie 2008, 2009Dewberry et al 2018Dewberry et al , 2019). It appears from our work that the short-wavelength limit of eccentric waves is important for the inner regions of XRBs, which is a nonlinear extension of those considered by Ferreira & Ogilvie (2008), Ferreira & Ogilvie (2009) in this context.…”
Section: Towards An Extension Of the Results Ofmentioning
confidence: 99%
“…Of particular relevance to this paper, the theory of Ferreira & Ogilvie (2009) predicts its own breakdown -with eccentric waves in the inner regions of black holes attaining very strong eccentricity gradients highlighting the need for a nonlinear theory to describe this regime. Ferreira & Ogilvie (2008) showed that the eccentricity gradients are important in determining the growth rates of inertial waves via a para-metric type instability, which have been proposed as the origin of high frequency quasi-periodic oscillations (QPOs) (Kato 2008;Ferreira & Ogilvie 2008, 2009Dewberry et al 2018Dewberry et al , 2019.…”
Section: Introductionmentioning
confidence: 99%